Trends in health system reorganization (2002)
As part of the analysis of the State's new role in health system management, some of the trends in such reorganization are examined: health sector guidance in relation to information systems and instances of consensus within the health sector; intersector and international coordination; exercising essential public health functions in aspects concerning their regulatory function, financing and implementing programs and attending disasters and emergencies; health sector financing according to resources, prioritizing of expenditure and subsidies; assurance and provision of services, emphasizing the transformation of public hospitals, costs, contractual systems and quality.